Adaptive systems in control and signal processing, 1989 : selected papers from the 3rd IFAC Symposium, Glasgow, UK, 19-21 April 1989 - Johnson, Michael A., 1948- (IFAC symposia series, 1990)
The Symposium covered three major areas: adaptive control, identification and signal processing. In all three, new developments were discussed covering both theoretical and applications research. Within the subject area of adaptive control the discussion centred around the challenges of robust control design to unmodelled dynamics, robust parameter estimation and enhanced performance from the estimator, while the papers on identification took the theme of it being a bridge between adaptive control and signal processing. The final area looked at two aspects of signal processing: recursive estimation and adaptive filters.